359 Switching from dupilumab to abrocitinib in patients with moderate-to-severe atopic dermatitis: an analysis of responders and nonresponders to dupilumab. (25th January 2023) - Silverberg, Jonathan I; Simpson, Eric L; Thyssen, Jacob P; Pink, Andrew E; Weidinger, Stephan; Chan, Gary; Lazariciu, Irina; Clibborn, Claire; Guler, Erman
Abstract: Abrocitinib, an oral, once-daily Janus kinase 1-selective inhibitor, had a superior efficacy vs. dupilumab in head-to-head randomized trials in moderate-to-severe atopic dermatitis (AD). Data on patients who switched from dupilumab to abrocitinib have been limited. To evaluate abrocitinib response in patients with moderate-to-severe AD who were responders or nonresponders to dupilumab. Dupilumab-treated patients from the JADE DARE trial (NCT04345367), which was designed to compare the efficacy and safety of 26-week abrocitinib (200 mg daily) vs. dupilumab (300 mg bi-weekly) in patients receiving topical medicated therapy, had the option to switch to abrocitinib 200 mg by enrolling to an open-label JADE EXTEND trial (NCT03422822). In this analysis, we evaluated the response to abrocitinib 200 mg at week 12 of JADE EXTEND of responders and nonresponders to dupilumab at week 26 of JADE DARE. Response and nonresponse were defined as patients' achievement and nonachievement, respectively, of ≥50%, ≥ 75% or ≥90% improvement from the JADE DARE baseline in Eczema Area and Severity Index (EASI-50, EASI-75 or EASI-90), ≥ 4-point improvement from JADE DARE baseline in Peak Pruritus Numerical Rating Scale (PP-NRS4), and PP-NRS score of 0 or 1 (PP-NRS 0/1) at week 26 of JADE DARE. In addition, changes in individual EASI and PP-NRS scores were evaluated in dupilumab-treated patients with significant skin lesions (EASI ≥16) or itch burden (PP-NRS ≥7) at week 26 of JADE DARE. Patients who withdrew from JADE EXTEND were considered nonresponders after withdrawal. Additionally, adverse events (AEs) of dupilumab-treated patients from JADE DARE occurring during JADE EXTEND were assessed. Out of 365 dupilumab-treated patients in JADE DARE, 312 received treatment in JADE EXTEND. After 12 weeks of switching to abrocitinib, EASI-50 response was maintained in 98% of patients (277/282) who had attained EASI-50 after 26 weeks of dupilumab. Those values were 95% (232/245) for EASI-75, 88% (143/162) for EASI-90, 91% (192/210) for PP-NRS4 and 79% (86/109) for PP-NRS 0/1. Conversely, among patients who did not attain EASI-50 after 26 weeks of dupilumab, switching to abrocitinib for 12 weeks resulted in 75% (12/16) of patients attaining this level of response. Those values were 77% (41/53) for EASI-75, 62% (85/136) for EASI-90, 51% (46/90) for PP-NRS4 and 45% (86/192) for PP-NRS 0/1. Among dupilumab-treated patients with EASI ≥16 at week 26 of JADE DARE, 91% (10/11) experienced improvements (i.e. EASI <16), after switching to abrocitinib for 12 weeks; in two such patients, score changes were consistent with ≥97% improvement in EASI from JADE DARE week 26 to JADE EXTEND week 12 (from 45.5 to 0 and from 42.3 to 1.4). Among patients with PP-NRS ≥7 at JADE DARE week 26, 75% (12/16) showed an improvement (i.e. PP-NRS score <7), 12 weeks after switching to abrocitinib; three such patients achieved a PP-NRS score of 0 or 1. During JADE EXTEND, 57% (178/312) of patients who previously received dupilumab experienced AEs and 3% (9/312) experienced serious AEs. Most patients with moderate-to-severe AD who switched from dupilumab to abrocitinib after 26 weeks maintained their response, while a great proportion of the nonresponders achieved clinically relevant efficacy outcomes 12 weeks after the switch. The safety profile of abrocitinib after switching from dupilumab was consistent with that of previous safety analyses; serious AEs were relatively rare.